VD_FINDINFO AI 5/12 - 249/2012 vom 30. Mai 2012 - VD Tribunal cantonal (2012)
AIASSURANCE, RENTEEN GÉNÉRAL, CALCUL, RECONSIDÉRATION | 36 al. 2 LAI, 29bis LAVS, 29quater LAVS, 29quinquies LAVS, 29sexies LAVS, 29ter LAVS, 30 LAVS, 30bis LAVS, 30ter LAVS, 33bis LAVS, 33ter LAVS, 53 al. 2 LPGA, 50 RAVS, 51 RAVS, 51bis RAVS, 52b RAVS, 52c RAVS, 52f RAVS